Chinese master’s students studying at a United Kingdom higher education campus in China: the impact of differences in learning dispositions - Waller, Stephen John (2020)
This research followed the transition of twelve Chinese students (studying business or social science subjects) from different Chinese learning environments to a UK Higher Education environment situated within a UK satellite campus in China. Using an interpretive research methodology, the participants were interviewed at different stages of one year of master’s study to discover their interpretations of the challenges they faced and their responses to these challenges. Drawing on the idea of learning dispositions and Bourdieu’s concept of hysteresis, the thesis proposes a model for the process that Chinese students undergo when they transfer from a Chinese education system to a UKHE setting. ! The findings of the research show that while learning experiences before the master’s study usually played a crucial part in the students’ preparation, those at their Chinese institutions did not provide the dispositions required for UK academic study. Although use of English and subject knowledge were major challenges, the new ways of studying and thinking also caused significant difficulties. Given time to adapt their learning dispositions, however, the students were capable of succeeding in their new learning environment. For some participants, more time was needed to adjust to UK academic study before the start of the master’s courses, while others needed less time because their learning experiences had already started to help their adjustment. Implications are drawn from the findings in relation to both students and institutions in support of the aim of achieving better teaching and learning experiences and outcomes.